AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI KAPULAGA JAWA (Amomum compactum Soland. ex Maton) TERHADAP Streptococcus pyogenes - Oom Komala; . Ismanto; Muhammad Alan Maulana (Universitas Pakuan, 2020)
Streptococcus pyogenes is one of the pathogenic bacteria that causes pharyngitis. Natural treatment to overcome these problems is to use cardamom seeds. The purpose of this study was to test the antibacterial activity, determine the concentration of inhibitory zone and phytochemical compounds from ethanol 96% extract of Java cardamom seeds (Amomum compactum Soland. Ex Maton) against Streptococcus pyogenes. The method is used solid dilution and paper disc diffusion method. The solid dilution method is used for the Minimum Inhibitory Concentration (MIC) test with a concentration of 1.25%, 2.5%, 5% and 7.5% while the paper diffusion method is used for the Inhibition zone Diameter (IZD) using five treatments namely three concentrations of ethanol 96% extract of Java cardamom seeds (7.5%, 10% and 12%), one positive control of amoxicillin 0.01 mg/mL and one negative control of sterile distilled water. IZD data were analyzed using ANOVA with a confidence level of 95% and α = 0.05 and Duncan's further tests to determine differences between treatments. The results showed that the MIC was at a concentration of 7.5% while for the IZD test which had the highest activity there was a concentration of 12% with an average inhibition diameter of 12.03 ± 0.14 mm. In addition, ethanol 96% extract of Java cardamom seeds contain alkaloids, flavonoids, terpenoids and tannins which function in antibacterial activity.